Evaluation of Pharmaceutical Aspects of Prescription Completeness at Hospital X in Lampung - Mohammad Thaha Husein Haikal; Rasmi Zakiah Oktarlina; Muhammad Yogie Fadli; Oktafany Oktafany (Sean Institute, 2026)
Prescription completeness is an essential component of pharmaceutical services as it is closely related to patient safety and the accuracy of drug therapy. Prescriptions that lack adequate pharmaceutical information may increase the risk of errors during the preparation and administration of medications. This study aimed to evaluate the completeness of prescriptions based on pharmaceutical aspects among outpatients at Hospital X in Lampung Province. A descriptive quantitative study with a cross-sectional design was conducted using secondary data from outpatient prescription records in October 2025. A total of 247 prescriptions were selected using a random sampling technique. Data analysis was performed using univariate analysis to describe the frequency distribution and percentage of completeness for pharmaceutical components, including drug name, dosage form, drug dose, quantity of drugs, and directions for use. The results showed that all prescriptions included the drug name (100%), while the quantity of drugs was documented in 99.2% of prescriptions. However, completeness in other components was still suboptimal, with drug dose documented in 62.8% of prescriptions, dosage form in 43.7%, and directions for use in only 23.5% of prescriptions. These findings indicate that although some pharmaceutical components have been documented, several essential prescription elements remain incomplete and may potentially affect the accuracy of pharmaceutical services. Therefore, improving adherence to prescription writing standards is necessary to support patient safety and the quality of healthcare services.